Current Controversies in Reverse Total Shoulder Arthroplasty. Issue 6 (14th June 2016) - Churchill, Jessica L.; Garrigues, Grant E.
Abstract : Reverse total shoulder arthroplasty can restore forward elevation in pseudoparalytic shoulders, can reduce pain, and can increase quality of life for patients; however, there are a number of issues with regard to the design and ideal implantation technique of reverse total shoulder arthroplasties that remain controversial. Glenospheres with a Grammont, medialized center of rotation and designs with a more lateralized center of rotation have specific pros and cons. Medialized designs have historically decreased glenosphere loosening but increase scapular notching, and lateralized designs decrease notching and improve range of motion but historically have resulted in increased baseplate failure. As such, a concrete conclusion with regard to medialization or lateralization of the glenosphere cannot be made at this time. Caudal, inferior placement of the glenosphere increases internal rotation, external rotation, abduction, and adduction while reducing notching. Superior baseplate positioning and tilt are correlated with baseplate failure and therefore should be avoided. It remains unclear whether neutral or slightly inferior tilt is preferred. The ideal humerosocket inclination angle remains unclear. The 135° designs appear to have a lower rate of scapular notching than the Grammont-style 155° humerosockets. The implications of this angle for instability remain unclear as, to our knowledge, there have been no randomized comparisons and the largest meta-analysis was confounded by other implant variables.